A Method for Preparation of Ordered Porous Silicon Based on a 2D SiO2 Template*Supported by the National Natural Science Foundation of China under Grant Nos 10804026 and 51101049, the Natural Science Foundation of Hebei Province under Grant Nos A2013205101 and A2014205051, and the Hebei Talent Cultivation Foundation under Grant No A201400119. (May 2016) - Wu 吴, Ying 英; Zhai 翟, Xiao-Xia 晓霞; Zhen 甄, Cong-Mian 聪棉; Liu 刘, Xiao-Wei 晓伟; Ma 马, Li 丽; Hou 侯, Deng-Lu 登录
Abstract : A new method for fabricating ordered porous silicon is reported. A two-dimensional silica nanosphere array is used as a template with a hydrofluoric acid–hydrogen peroxide solution for etching the nanospheres. The initial diameter and distribution of the holes in the resulting porous silicon layer are determined by the size and distribution of the silica nanospheres. The corrosion time can be used to control the depths of the holes. It is found that the presence of a SiO2 layer, formed by the oxidation of the rough internal surface of the hole, is the primary reason allowing the corrosion to proceed. Ultraviolet reflection and thermal conductivity measurements show that the diameter and distribution of the holes have a great influence on properties of the porous silicon.